Hiệu quả của việc xây dựng algorit biến đổi bài toán để tìm lời giải nhằm phát triển năng lực giải quyết vấn đề và sáng tạo trong dạy học môn Hóa học ở phổ thông - Nguyễn, Thị Bích Hiền; Mai, Quỳnh Châu (Tạp chí Giáo dục, 2025)
This study focuses on experimenting with the requirement for students to construct algorithms for transforming problems to identify problem-solving approaches, viewing the problem as an active teaching tool to develop students’ problem-solving creativity competence. To evaluate students’ progress in problem-solving competence and creativity through problem solving activities, we used an assessment rubric based on a 5-point Likert scale. The research findings indicate that constructing algorithms for transforming problems prior to solving them positively impacts the development of problem-solving creativity competence, particularly in components such as problem identification, hypothesis formation, and planning problem-solving strategies. This provides a basis for further dissemination of the method to teachers to enhance students’ problem-solving creativity competence, thereby improving the overall effectiveness of teaching and learning in high schools.